(untitled) (The International Journal for Scientific Research, 2024)
This study aimed to identify the impact of using social media on organizational performance in small projects for female entrepreneurs in the application of the CURA project. To achieve the study objectives, the quantitative approach was used, and the questionnaire was used as a tool to collect data from the intentional study sample, which consisted of 170 individuals on the CURA project. 124 questionnaires were retrieved with a response rate of 73%, and analyzed using the multiple variance test using the SPSS statistical analysis package. The results of the study concluded that there is a statistically significant positive impact of using social media on organizational performance in its dimensions (time to market - satisfaction - innovation) in the application of the CURA project. The study recommended the need to work on activating social media on the widest scale due to its great importance in communication processes and the tremendous development in modern applications, by finding specialists or specialized departments in small projects to care about social media and work to activate it in the best possible way.